ANALISIS USAHA PRODUK KERUPUK “ABIDZAR” DI DESA UJUNGPANGKAH DENGAN METODE SMART BUSINESS MAP - Elif Nashikhatul Maziyah; Vembri Aulia Rahmi (Universitas Muhammadiyah Gresik, 2023)
This study aims to analyze Small, Micro and Medium Enterprises (MSMEs) of processed cracker products in UjungPangkah Village using 3 informants, namely 1 owner and 2 workers, 8 consumers and 3 competitors. The research was conducted using a qualitative descriptive analysis method with the Smart Business Map (SBM), namely analyzing the Playing Field, Market Landscape and Operational Profitability sections. This research can be used by MSME processed crackers in determining business direction, market share, compliance with customer needs, appropriate appropriate technology to increase revenue. The results of the analysis using the SBM method show the health condition of the business which will later identify problems in it that need to be implemented immediately by a new strategy or solution. This study has limitations on the research object, which is only focused on cracker traders and parameters that are seen only on the health of the Abidzar cracker MSE business.